The truth about lies in the workplace : how to spot liars and what to do about them - Goman, Carol Kinsey (Berrett-Koehler Publishers, 2013)
Lies aren't good in general, but in the workplace they're especially poisonous. They can destroy employee engagement and productivity, undermine teamwork, increase stress, ruin people's livelihoods, and even bring down entire companies. It's critical to catch workplace lies before they snowball into something catastrophic, but most of us have no clue about how to spot a liar. And the workplace setting adds another layer of complexity. At what point do you report a liar? If you decide to take action, what exactly should you do? And what if the liar is your boss? In this entertaining and needed book, leading workplace body language expert Carol Kinsey Goman combines her own experiences with the latest research to provide a comprehensive guide to spotting, exposing, and minimizing workplace lies. Goman looks at the high cost of workplace deception for individuals and organizations, why people tell lies at work, and the kinds of lies they tell. She offers fifty ways that body language and vocal cues can help you spot a liar and explains how our own vanities, desires, self-deceptions, and rationalizations allow us to be duped. Once you spot a lie, she provides tactical advice on how to respond, whether the liar is above, below, or on the same level as you. And Goman explains how to make sure your own body language doesn't inadvertently make you seem untrustworthy and what leaders at all levels can do to reduce lies and encourage candor. Some workplace lies are a polite and positive part of professional life ("I'd be delighted to come to that meeting"). But Goman focuses on truly destructive lies and shows how you can prevent them from wreaking havoc on individuals and organizations.--Publisher description.